THE CORRELATION BETWEEN CHLOROPHYLL-A AND SEA SURFACE TEMPERATURE BASED ON THE IMAGE OF A AQUA MODIS SATELLITE WITH THE CATCH OF YELLOWSTRIPE SCAD (Selaroides leptolepis) IN THE WATERS OF THE EAST COAST OF SUMATERA - Sarah Adriani R. S; Arthur Brown; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTsarah.adriani@gmail.comThe aim of this study was to determine the variability of the concentration of chlorophyll-a and sea surface temperature (SST) as well as its relationship with the catch of yellowstripescad(Selaroides leptolepis) in the waters of the coast of Sumatera. The value of SST and chlorophyll-a concentration was obtained from MODIS. While the data of yellowstripescad(Selaroides leptolepis) obtained from the PelabuhanPerikananSamudera Belawan. The highest yellowstripescadcaught in the East season and the second transition season with an average catch of 3529kg/year and 3549.4kg/year. In the east season the average chlorophyll-a was 0.76 with a range0.2mg/m3-1.36mg/m3 and an average sea surface temperature of 30.03oC with a range of 28.54oC-30.93oC. In the transitional season II averages of chlorophyll-a 1.15 with a range of 0.61mg/m3-1.99mg/m3 and average sea surface temperature of 28.88oC with a range 27.45oC-29.96oC. The west season is the most dominating of the chlorophyll-a concentration of about 3.93mg/m3. The SST of Malacca Strait is following of the wind pattern that occurred in Indonesian water. On fluctuations in chlorophyll-a and catches in the East season and transition season II explain that the decrease in chlorophyll-a concentration is inversely proportional to the fluctuations in catches, while fluctuations in sea surface temperature and catches in the East season and transition season II have and influence on the rise and fall of sea surface temperature. Correlation r2 between catches with clorophyll-a and sea surface temperature are very weak (r= 0.12) or the contribution of chlorophyll-a and sea surface temperature only 1.4% forward the yellowstripescad catches.Key word :Aqua MODIS, Chlorophyll-a and Sea SurfaceTemperature and Selaroides leptolepis.